Análisis técnico y periodístico del noticiero mundovisión del canal de televisión ecotel tv, periodo (febrero – marzo de 2019). - Guaman Tacuri, Jose Wladimir (2019)
The present investigative work focuses on analyzing the Mundovisión Newsreel of the Ecotel TV Channel of the city of Loja. The general objective is to analyze the technical aspect and the news newspaper Mundovisión of the television channel Ecotel TV, in the period November 2018 - February 2019, where four elements will be studied: content, focus, technical aspect and journalistic criteria in their broadcasts. This research has a review of the literature, where to find the theoretical concepts necessary for this work; the results were obtained with the application of a single research instrument. This was the Vertical Sweep Table, in which all the news broadcasts of the Ecotel TV television channel were analyzed over a month. Four vertical sweeping tables were taken into account based on compliance with the proposed objectives. The first consisted of an analysis of the contents presented in the Ecotel TV news. The second corresponded to the focus of these contents, that is, the way in which they are presented. The third table was an analysis of the technical aspects of the production of this newscast. Finally, in the fourth table, it was analyzed the journalistic criteria with which the information is presented in this media, although it is true that it is similar to the second table, it becomes more specific. After this is the discussion, where the results are compared with the objectives and then the elaboration of the conclusions and recommendations. Finally, as a proposal, a Newscast Model for the Ecotel TV Television Channel is included.